Design and Implementation of A Forward-Reverse Double-Speed Three-Phase Induction Motor Control System Based on A Programmable Logic Controller - Abdul Muis Prasetia; Linda Sartika; Danny Arans Sevri Andika (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
The Dahlander motor is an asynchronous AC motor that operates at two or more distinct rotational speeds, making it different from standard three-phase motors, which generally maintain a single speed under the same power conditions. This motor features a squirrel-cage rotor design and is integrated with a programmable logic controller (PLC), which simplifies wiring systems and allows operational adjustments without altering the wiring layout. However, an additional component, the selector switch, is also employed. This switch controls the motor's rotational direction, enabling it to rotate either clockwise or counterclockwise. The study utilizes a quantitative approach with a developmental design to assess the performance of the Dahlander motor control system. The system functioned as expected, with the selector switch responsible for changing rotational direction. In the right position, pressing the ON 1 button activates contactor 1 for slow clockwise rotation, while pressing ON 2 activates contactors 2 and 3 for fast clockwise rotation. In the left position, pressing ON 1 activates contactor 4 for slow counterclockwise rotation, and pressing ON 2 activates contactors 5 and 6 for fast counterclockwise rotation. The measured rotational speeds were as follows: during slow clockwise rotation, the rotor reached 1494 rpm, while for fast clockwise rotation, it hit 3055 rpm. During slow counterclockwise rotation, the rotor speed was 1456 rpm, and for fast counterclockwise rotation, it reached 3050 rpm.